Larger tumors are associated with inferior progression‐free survival of first‐line EGFR‐tyrosine kinase inhibitors and a lower abundance of EGFR mutation in patients with advanced non‐small cell lung cancer - Yingying Pan; Guanghui Gao; Xiaoxia Chen; Qinrui Tian; Fengying Wu; Qian Liu; Yan Wang; Tao Jiang; Yiwei Liu; Xuefei Li; Shuo Yang; Chuan Xu; et al. (Thoracic Cancer, 2019)
Background The impact of primary tumor size on the therapeutic outcomes of EGFR‐tyrosine kinase inhibitors (TKIs) in advanced non‐small cell lung cancer (NSCLC) with EGFR mutation remains unclear. Methods A total of 291 consecutive patients with advanced EGFR‐mutant NSCLC administered first‐line EGFR‐TKIs were enrolled. Computed tomography was used to assess primary tumor diameter. The amplification refractory mutation system plus was used to quantitatively evaluate the abundance of EGFR mutations. Associations between depth of response, abundance of EGFR mutations, and tumor size was investigated. Results Patients were divided into three groups according to T classification: ≤ 3 cm (n = 109), 3–5 cm (n = 121), and > 5 cm (n = 61). Median progression‐free survival (PFS) was significantly longer in the ≤ 3 cm and 3–5 cm groups compared to the > 5 cm group (10.8 vs. 10.5 vs. 7.1 months; P < 0.001). Subgroup analysis revealed a consistent result in patients with exon 19 deletion and 21 L858R mutation. Multivariate analysis revealed that tumor size was an independent predictive factor for PFS (hazard ratio 1.528, 95% confidence interval 1.104–2.115; P = 0.010). Larger tumors (> 5 cm) were marginally significantly less EGFR‐mutant abundant than smaller tumors (≤ 5 cm) (mean ± standard deviation 30.5 ± 29.5% vs. 45.8 ± 43.1%; P = 0.08). Conclusion Larger tumors (> 5 cm) were associated with inferior PFS of first‐line EGFR‐TKI therapy in advanced NSCLC patients with activating EGFR mutations. A potential explaination might be that EGFR mutations are less abundant in larger tumors.